(untitled) (Research, Society and Development, 2022)
The objective of the present study was to evaluate the intensity of weight loss in beef heifers during gestation and its effects on progeny performance up to 205 days of age. Sixty pregnant heifers aged 3 or 4 years, born between 2015 and 2017, from the rotational cross between Charolais and Nellore breeds were used. Females were divided according to the intensity of weight loss in the gestation period (7, 14, and 21%) and age at first calving (3 and 4 years), in a completely randomized design in a 3 x 2 factorial scheme. Lost up to 21% (T21) of body weight during gestation and had higher body conditions at the end of the breeding season (3.12 vs 3.02 and 3.04 points) and lower body weight at calving (341.96 vs 386.26 and 362.95 kg) about T7 and T14 heifers. The birth weight of the calves showed a tendency to increase as the weight loss of the pregnant heifers increased, with values of 29.46, 30.60 and 32.76 kg for treatments T7, T14 and T21, without reflections on the post-weaning performance of the progeny. In general, the loss of 14 or 21% of the heifer’s body weight during pregnancy reduces the weight at the first calving, while heifers calved at 4 years of age are heavier and give rise to progeny with greater productive potential up to 205 days of age.